State of emergency: The Geopolitics of puzzling (Revista LIDER, 2020)
While the army takes to the streets, the legal doctrine moves more and more closer towards a guaranteed framework that will give recognition to the indigenous community's right to be consulted. Unfortunately, this is not worth the paper it's written on when they have to face such heavy artillery. This avoids recognizing the complicated and pluralist reality, where justice is not consulted but remains a production of reality and where the army is one step closer towards reaffirming the narcopolitics of Mexico's new regime. We, however, present cartography of judicial resistance, of archipelagos in the midst of a new variant of commercial reservation or of the permanent state of exception.